2020
DOI: 10.1038/s41598-020-74586-9
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community dynamics in phyto-thermotherapy baths viewed through next generation sequencing and metabolomics approach

Abstract: Phyto-thermotherapy is a treatment consisting in immersing oneself in baths of self-heating alpine grass, to benefit of the heat and rich aromatic components released by the process. The aim of this study was to characterize the bacterial and fungal diversity of three phyto-thermal baths (PTB) performed in three different months, and to compare the data with the profile of the volatile organic compounds (VOCs) of the process. All the data collected showed that PTBs were structured in two stages: the first thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Also, the osmotic shock was used for liberating the pigmented products, especially just in the case of halophilic archaea bacterial strains as reported by Hagazy et al [ 21 ]. Additionally, many protocols for pigment extraction are usually followed using different solvents like hexane, benzene, chloroform, methanol, acetone, ethanol, or mixed solvent [ 35 ]. However, during this study, successful extraction for LS1 pigment was observed by using the organic solvent ethanol with a purity of 99.9% (at a volume ratio 1:1).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the osmotic shock was used for liberating the pigmented products, especially just in the case of halophilic archaea bacterial strains as reported by Hagazy et al [ 21 ]. Additionally, many protocols for pigment extraction are usually followed using different solvents like hexane, benzene, chloroform, methanol, acetone, ethanol, or mixed solvent [ 35 ]. However, during this study, successful extraction for LS1 pigment was observed by using the organic solvent ethanol with a purity of 99.9% (at a volume ratio 1:1).…”
Section: Discussionmentioning
confidence: 99%
“…Its relative abundance was always <1% with the exception of Mfarm N, in which it was the dominating taxa and driver characterizing the TMB samples (relative abundance of 23.1%). Erwinia are herb-associated bacteria found in high relative abundances in some Alpine herbs in the Trentino highland in the summer season [43] and can, thus, be introduced into raw milk by a cross-contamination of pasture herbs microbiota. Leuconostoc (driver at Mfarm C) and Streptococcus (driver at both Mfarms B and O) are the most common LAB genera found in milk and dairy products besides Lactococcus [2].…”
Section: Taxonomic Composition Of the Bacterial Communitymentioning
confidence: 99%
“…269 Studies have found that the intervention of external stimulation in the regulation of body temperature can change the physiological process of the body and even realize the treatment of diseases. 119,270–272 Local hyperthermia has become a powerful tool for treating solid tumors. 273–277 During treatment, tumor tissue is heated to over 50 °C, which initiates a strong cytotoxic effect and causes tumor cell necrosis.…”
Section: Introductionmentioning
confidence: 99%